Cultural Threats in Culturally Mixed Encounters Hamper Creative Performance for Individuals With Lower Openness to Experience. (November 2016) - Chen, Xia; Leung, Angela K.-y.; Yang, Daniel Y.-J.; Chiu, Chi-yue; Li, Zhong-quan; Cheng, Shirley Y. Y.
Past research has examined independently how openness to experience, as a personality trait, and the situational threat triggered by a foreign cultural encounter affect the emergence of creative benefits from a culture-mixing experience. The present research provides the first evidence for the interactive effect of openness to experience and cultural threat following culturally mixed encounters on creative performance. In Study 1, under heightened perceptions of cultural threat, exposing to the mixing of Chinese and American cultures (vs. a non-mixed situation) made close-minded Chinese participants to perform more poorly in a creative generation task. In Study 2, inducing cultural threat by having a foreign cultural icon spatially intrude a sacred space of the local culture caused Chinese participants with lower levels of openness to perform less creatively when the foreign icon was deemed highly symbolic of the foreign culture. These patterns of effects did not emerge among open-minded participants. These findings suggest that trait openness acts as a buffer against foreign cultural threat to sustain the creative benefits of culture mixing.